Pengaruh Pemasaran Digital dan Citra Destinasi Terhadap Keputusan Berkunjung di Desa Wisata Lebakmuncang Kabupaten Bandung - Arvianida Nafisah Rachmidiani; Emron Edison (STIEPAR YAPARI Bandung, 2023)
This research aims to analyze the influence of digital marketing and destination image on the visiting decision in Lebakmuncang Tourism Village, Bandung Regency. The research method used is quantitative with descriptive and verification analysis. The analytical technique employed is Multiple Linear Regression. The population of this study consists of tourists who visit Lebakmuncang Tourism Village, with a sample size of 100 respondents. Data were collected using questionnaires distributed to visitors of Lebakmuncang Tourism Village. The descriptive results of the study indicate that all variables are categorized as